Analysis of shots in relation to the outcome in elite women's water polo matches. - Menescardi, C.; Tessitore, A.; Estevan, I.; Condello, G.; Lupo, C. (Revista Internacional de Ciencias del Deporte, 2018)
The aim of the current study was to investigate the shot performance of elite female water polo players according to their match outcome during three international tournaments, the 2012 Olympic Games, 2013 and 2014 FINA World Leagues. Twenty-four official matches footage [2012 Summer Olympic Games, n=8; 2013 FINA World League, n=8 and 2014 FINA World League, n=8] were obtained and analysed. The results showed that a similar playing style was used in both the 2012 and 2013 tournaments, independently of the outcome while in the 2014 FINA World League, winning teams performed more shots after displacement, more shots ending to zone 4 and scored more goals than losing ones (and fewer shots against posts), highlighting a greater ability to create team opportunities and score a goal. In addition, teams` behaviour changed over time: teams opted to perform more counterattacks and less power play situations. In addition to a more zonal defence, as time passes, probably to limit the play action of the opponent centre forward players. Teams also modified the type of shots performed to make them less predictable and to adapt them to each playing situation.